The Place of the Sacred in Cassirer’s Philosophy of Mythology - Moss, Gregory S (Studia Kantiana, 2023)
In this essay I defend Cassirer’s account of mythical culture against a series of critiques raised against his philosophy of mythology. Cassirer has been charged with neglecting the profane dimension of mythical culture and with presenting an inconsistent account of sacred being. In order to make headway on these critiques, I first demonstrate that Cassirer does in fact acknowledge the profane and its place in mythical culture. Through close conceptual and textual analysis, I reconstruct Cassirer’s account of the sacred and the profane in “Myth as Form of Intuition” in the second volume of the Philosophy of Symbolic Forms. After demonstrating the presence of this distinction in Cassirer’s texts, I reconstruct Cassirer’s account of the emotive origin of the sacred in mythical culture. Finally, I show how Cassirer’s the law of mythical culture is not inconsistent with the sacred, but is a further articulation of the form of sacred being.